Soccer coaches' and referees' perceptions of tackle incidents with respect to the laws of the game - Coleclough, J. (International Journal of Performance Analysis in Sport, 2013)
The purpose of the current investigation was to examine the perceptions of coaches and referees about decisions made by the match referees about player to player contact situations during the UEFA Euro 2012 soccer tournament. A video was produced of 106 incidents and analysed with respect to the laws of the game. The match referees made the correct decision for 91 of the 106 incidents and applied the correct sanction for 88 of the incidents. Seven coaches and six referees viewed the video indicating whether or not they agreed with the match referees' decisions and sanctions, providing supporting comments where they disagreed. The correctness of the coaches and referees decisions was similar to that of the match referees. The supporting comments revealed that the four elements of Mascarenhas et al.'s (2005) 'Cornerstones Model' developed for rugby union refereeing were all transferrable to soccer refereeing. The study found that refereeing decisions involve interpretation of the laws of the game. The participants perceived that decisions were influenced by contextual factors, referees needed to balance game management and control with correct application of the laws of the game and that referee movement and positioning was important to good decision making.